Glucose sensing by regulator of G protein signaling 1 (RGS1) plays a crucial role in coordinating defense in response to environmental variation in tomato. Issue 2 (17th August 2022) - Wang, Jiao; Wang, Anran; Luo, Qian; Hu, Zhangjian; Ma, Qiaomei; Li, Yimei; Lin, Teng; Liang, Xiao; Yu, Jingquan; Foyer, Christine H.; Shi, Kai
Summary: Low light intensities affect the outbreak of plant diseases. However, the underlying molecular mechanisms remain poorly understood. High‐performance liquid chromatography analysis of tomato ( Solanum lycopersicum ) revealed that apoplastic glucose (Glc) levels decreased in response to low light. Conversely, low‐light‐induced susceptibility to Pseudomonas syringae pv tomato ( Pst ) DC3000 was significantly alleviated by exogenous Glc treatment. Using cell‐based biolayer interferometry assays, we found that Glc specifically binds to the tomato regulator of G protein signaling 1 (RGS1). Laser scanning confocal microscopy imaging revealed that Glc triggers RGS1 endocytosis, which influences the uncoupling of the RGS1‐Gα (GPA1) and GPA1‐Gβ (SlGB1) proteins, in a dose‑ and duration‐dependent manner. Analysis of G protein single and double mutants revealed that RGS1 negatively regulates disease resistance under low light and is required for Glc‐enhanced defense. Downstream of RGS1‐Glc binding, GPA1 negatively mediates the light‐intensity‐regulated defense, whereas SlGB1 positively regulates this process. These results reveal a novel light‐intensity‐responsive defense system that is mediated by a Glc–RGS1–G protein signaling pathway. This information will be critical for future investigations of how plant cells sense extracellular sugars and adjust defense under different environments, as well as for genetic engineering approaches to improve stress resilience.